1996
DOI: 10.1046/j.1365-2141.1996.7292351.x
|View full text |Cite
|
Sign up to set email alerts
|

IN VIVO MOBILIZATION OF KARYOTyPICALLY NORMAL PERIPHERAL BLOOD PROGENITOR CELLS IN HIGH‐RISK MDS, SECONDARY OR THERAPY‐RELATED ACUTE MYELOGENOUS LEUKAEMIA

Abstract: We have previously reported that mobilization of Philadelphia (Ph) chromosome-negative progenitors is possible in a significant number of Ph1-positive acute lymphoblastic leukaemia (ALL) and chronic myelogenous leukaemia (CML) patients. In this pilot study we employed the same approach for patients with RAEB-t, secondary AML (sAML) and therapy-related AML (t-AML). All patients except one had double or complex cytogenetic abnormalities in marrow cells before mobilization therapy. All patients received an idarub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 6 publications
0
38
0
2
Order By: Relevance
“…As for mini-ICE, consolidation with intermediate/ high-dose cytarabine7etoposide has been associated with adequate collection of PBSC in patients with AML. 13,14,20,26 Thus, it is tempting to speculate that the idarubicine component may have had a negative impact on mobilisation. Indeed, certain chemotherapeutic drugs, such as fludarabine, have been reported to impair mobilisation of PBSC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As for mini-ICE, consolidation with intermediate/ high-dose cytarabine7etoposide has been associated with adequate collection of PBSC in patients with AML. 13,14,20,26 Thus, it is tempting to speculate that the idarubicine component may have had a negative impact on mobilisation. Indeed, certain chemotherapeutic drugs, such as fludarabine, have been reported to impair mobilisation of PBSC.…”
Section: Discussionmentioning
confidence: 99%
“…11 On the other hand and arguing against a negative role of idarubicine, several previous investigators have reported a high percentage of successful PBSC collections in AML patients following consolidation with combination CT including idarubicine or other anthracyclines ( þ G-CSF). 8,14,27,28 The optimal scheduling of G-CSF, as combined with CT for mobilisation of PBSC, is not known and may depend on the CT regimen used. 12 In most protocols, G-CSF is started 1-2 days after CT and administered once daily until completion of leukapheresis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations